Improving slurry dewatering performance of basket centrifuge: discharge of supernatant using bypass filter medium - Ginting, Alvin Najmuddin; Fukuyama, Ryo; Jami, Mohammed Saedi; Tanaka, Takanori; Iwata, Masashi (The Society of Chemical Engineers, Japan, 2015)
In order to improve the performance of the centrifuge, a new design of dewatering of slurry which forms less permeable cake is proposed. In the proposed design, the filter media is placed not only on the circuit, but also at the bottom of the filter chamber. The additional bottom filter medium is expected to work as a bypass. The comparison of the conventional and new designs is made in this study. The supernatant is completely discharged in much shorter time when the new method is used; hence the filter medium at the bottom of the filter chamber works as a bypass and improved the dewatering performance.